Jurnal Pendampingan Pengolahan dan Pembuatan Teh Kombucha Penuh Manfaat Bagi Kesehatan Terhadap Pemuda-Pemudi Majlis Taklim Ar-Rahman Kabupaten Garut - Jafar Amirudin; Iis Komariah; Ani Yanti Ginanjar; Megawati Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
The purpose of this service is to assist the youth community, with the many benefits obtained from Kombucha Tea, it is hoped that this will become a typical Garut souvenir that can be of interest to the wider community, as well as an alternative drink to treat various health problems in the community, so that this will open up new jobs for the community. The implementation of this activity was carried out at the Majlis Taklim ar-Rahman in Sukaresmi Garut with 30 participants. The method used in this service is Participatory Action Research (PAR), which means that the community service actors directly experience the assistance of making kombucha tea in the field with the community. There are four basic themes in PAR, namely collaboration through participation, gaining knowledge, and social change. The results of this kombucha tea making assistance are making tea from available kombucha seeds, then conducting training from a certified kombucha expert and mentoring in making kombucha tea as well as packaging training and business strategies to market the products that have been produced.